Sex Differences in Revascularization, Treatment Goals, and Outcomes of Patients With Chronic Coronary Disease: Insights From the ISCHEMIA Trial - Reynolds, Harmony R; Cyr, Derek D; Merz, C Noel Bairey; Shaw, Leslee J; Chaitman, Bernard R; Boden, William E; Alexander, Karen P; Rosenberg, Yves D; Bangalore, Sripal; Stone, Gregg W; Held, Claes; Spertus, John; et al. (Wiley, 2024)
Women with chronic coronary disease are generally older than men and have more comorbidities but less atherosclerosis. We explored sex differences in revascularization, guideline-directed medical therapy, and outcomes among patients with chronic coronary disease with ischemia on stress testing, with and without invasive management.
Keywords: coronary artery disease; ischemic heart disease; sex differences; women's health